Impact of technology on PLL power and frequency - Sulaiman, Mohd-Shahiman (2006)
Purpose - This paper presents a prediction on the impact of technology scaling on phase-locked loop (PLL) performance behaviour. Power and maximum operating frequency of an Analogue PLL and a Type II phase-frequency detector (PFD)-based PLL from which the behaviours of other PLLs derived from the two architectures can be estimated, are analysed and their future behaviours as a function of technology are predicted.